Cross Cultural Marketing Challenges- A Case Study of Select MNC's - Sambrani, Smitha (Indian Journal of Marketing, 2006)
The global economic boom unpreceeded in modern economic history, has seen efficiency, productivity and open unregulated markets sweep the world. Today, most domestic businesses have become deeply involved and affected by international global businesses. Powerful economic, technological, industrial, political, demographic and cultural forces are converging to build the foundation for a new global business order in which the structure of a one world economic and market system is emerging. It is here that cross-cultural marketing is gaining all the more predominance. Cross cultural marketing that can be defined, as the performance of business activities that directs the flow of a company's products and services to consumers or users in more than one nation for a profit is a complex and diverse concept. While the business' goal of making a profit by promoting, pricing and distributing its products for which there is a market remains the same, the challenge comes from the environment in which the marketing plan must be implemented. The uniqueness of cross cultural marketing comes from the range of unfamiliar problems and the variety of strategies necessary to cope with different levels of uncertainty encountered in foreign markets. Political/legal factors, economic climate, level of technology, class structure, competition, geography, infrastructure and cultural forces are some of the uncontrollable elements that affect the profitable outcome of a good sound marketing plan. While it is difficult for a marketer to control or influence these elements the real challenge lies in moulding the controllable elements of marketing decisions like product, price, promotion and distribution within the framework of the uncontrollable elements of the market place in such a way that marketing objectives can be achieved. This paper presents a case study of four companies: Levi Strauss, Nike, General Motors and Electrolux who inspite of being global leaders in their respective segments found it a daunting task to handle the cross cultural marketing challenge in the Indian context.